2013
DOI: 10.1021/jp402007z
|View full text |Cite
|
Sign up to set email alerts
|

Mg-Doped CuFeO2 Photocathodes for Photoelectrochemical Reduction of Carbon Dioxide

Abstract: Mg-doped CuFeO 2 delafossite is reported to be photoelectrochemically active for CO 2 reduction. The material was prepared via conventional solid-state methods, and subsequently assembled into an electrode as a pressed pellet. Addition of a Mg 2+ dopant is found to substantially improve the conductivity of the material, with 0.05% Mg-doped CuFeO 2 electrodes displaying photocathodic currents under visible irradiation. Photocurrent is found to onset at irradiation wavelengths of ∼800 nm with the incident photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 44 publications
3
134
0
1
Order By: Relevance
“…Gu et al reported that the Mg-doped delafossite CuFeO 2 can act as a photoelectrocatalyst under illumination of <800 nm light. 233 Although this system can be used to reduce CO 2 to formate at an underpotential of approximately 400 mV, the Faradaic efficiencies are generally poor, with a maximum efficiency of 10% at −0.9 V vs SCE.…”
Section: +mentioning
confidence: 99%
“…Gu et al reported that the Mg-doped delafossite CuFeO 2 can act as a photoelectrocatalyst under illumination of <800 nm light. 233 Although this system can be used to reduce CO 2 to formate at an underpotential of approximately 400 mV, the Faradaic efficiencies are generally poor, with a maximum efficiency of 10% at −0.9 V vs SCE.…”
Section: +mentioning
confidence: 99%
“…In 2013, a Mg-doped CuFeO 2 delafossite photocathode was fabricated to achieve the PEC reduction of CO 2 to formate [95]. The Mg 2+ dopant extended the absorption of visiblelight and improved the conductivity of photocathode, offering an FE of 10% at −0.9 V versus SCE and an incident photon-to-current efficiency (IPCE) value of 14% at 340 nm using an applied potential of −0.4 V versus SCE.…”
Section: Dopingmentioning
confidence: 99%
“…30 The conduction band edges could be calculated by subtracting the measured band gaps from the valence band edges. Flat band potential (V f ) can be calculated by subtracting k B T/e from the x-intercept in the linear plot of 1/C 2 vs V. The negative slope of Mott-Schottky plots means the p-type property of semiconductor and vice versa.…”
Section: Band Characterization Using Mott-schottky Plotsmentioning
confidence: 99%